KEDUDUKAN HUKUM TANAH REVITALISASI PERKEBUNAN YANG DITELANTARKAN (STUDI KASUS PENYELESAIAN SENGKETA LAHAN ANTARA KELOMPOK TANI MAJU JAYA DENGAN PT. BUMI DAYA ABADI PADA LAHAN 226 HA DESA MUKTI LINCIR KECAMATAN KOTA BAHARU) - FIRMAN SAPUTRA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. T. Keizerina Devi A3. Syafnil Gani Plantation revitalization is the effort to accelerate the development of smallholdings by expansion, rejuvenation and plant rehabilitation supported by loan investment from bank and subsidy from government. It involves companies in plantation field to be partners to develop the plantation, manufacturing and product marketing. However, there are several problems concerning the land in the plantation revitalization program i.e. a dispute over a piece of land between Maju Jaya Farming Group and PT. Bumi Daya Abadi in Kota Baharu Subdistrict. This thesis applies normative legal research which is descriptive analytical. It uses secondary data consisting of primary data such as the Constitution 1945, the Law No. 5/1960 concerning the Basic Regulations on Agrarian Principles, the Law No. 39/2014 concerning Plantation, Regulation of Head of National Land Department no. 4/2010 concerning the Procedures for the Issuance of Abandoned Land. The secondary legal materials consist of books, and the tertiary data are general and legal dictionaries The legal protection for the member farmers for the act done by their business partners who have abandoned the plantation revitalization land which has not been protected; the legal protection for the government is that it can revoke the license of the relevant plantation company; the legal protection for the business partner is that it has fulfilled its rights as executor of the revitalization program such as paying the expenses during the program and the commissions of the business partners. The efforts of the government to settle the dispute over the land between Maju Jaya Farming Group and PT. Bumi Daya Abadi against the plantation revitalization land that has been abandoned are providing mediation among the involved parties directly from the revitalization program by the regional administration to reappraisal.Keywords: Revitalization, Plantation, Land Dispute.